Recent Innovative Technologies For Catalytic Decomposition Of Volatile Organic Compounds (VOCs) In Air Stream. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2001)
This article presents recent reseachers done in developing new and innovative technologies for VOCs catalytic decomposition.